Finite element analysis of Kirschner wire fixation for lateral condyle fracture in children in the sagittal plane - Bai, Huanan; Lu, Qingda; Liang, Xiaoju; Wang, Xiaoming; Yang, Yating; Wang, Huan; Wang, Jiaju; Jie, Qiang (Frontiers in Pediatrics, 2023)
This study aims to find the optimal arrangement of K-wire in the sagittal plane for fixation of a pediatric lateral condylar humeral fracture(Milch type II) by using finite element analysis(FEA).Methods A model of lateral condyle fracture in a 6-year-old boy was developed, and an XYZ coordinate system was established based on this model. The YZ plane was defined as the sagittal plane to investigate the impact of the angle formed by the first and second K-wire on stability. Two configurations were studied for each angle: parallel and divergent. Evaluation indicators included the maximum displacement of the fracture fragment and the maximum Von Mises stress in the pins and bone.The model with a -60°angle showed the best performance in both evaluation indicators. The parallel and divergent pin configurations had different performances in each group. The displacement results for negative angles were similar, and this result was better than those for positive angles.We successfully created a model of pediatric lateral condyle humerus fracture(Milch type II) and performed K-wires fixation with varying sagittal plane configurations, combined with FEA. Our findings demonstrate that the angle of -60°29